Healthcare workers 'on the move': making visible the employment-related geographic mobility of healthcare workers. Issue 3 (2nd September 2019) - Jackson, Lois; Price, Sheri; Gardiner Barber, Pauline; Kruisselbrink, Audrey; Leiter, Michael; Nourpanah, Shiva; Bourgeault, Ivy
ABSTRACT: Many healthcare workers are 'on the move' as part of their employment, travelling often great distances to such places as patients'/clients' homes and community clinics. Healthcare workers' experiences of this employment-related geographic mobility have been relatively invisible even though mobility is necessary for home and community care. Interviews with professional (e.g. nurses) and paraprofessional (e.g. personal care assistants) healthcare workers in Nova Scotia (Canada) found that mobility includes safety risks, and health and economic costs, although a few professionals had employment contracts that helped to protect them against such risks and costs. Paraprofessionals appear to be most impacted by the economic costs given their lower incomes. Many healthcare workers also experienced travel positively, as time away from fixed sites, and associated this time with freedom. The risks of mobility were understood by some workers as part of a duty to care, but a few suggested that the health and economic costs are an undue burden, pointing to an opening for challenging these conditions. There is a need for regulations to ensure all healthcare workers are safe as they are mobile to and from fixed sites, and do not have to shoulder the health or economic costs of mobility.